An understanding of the concept of knowledge management for knowledge management system implementation in two mobile telecommunication companies in Namibia - Mubuyaeta, Mishake Mitchell; Ponera, Jaffar Msafiri (University of Dar es Salaam Library Journal, 2024)
This study investigates the understanding of knowledge management (KM) for knowledge management systems (KMS) implementation for efficient KM practice in two mobile telecommunications (MT) companies in Namibia. Using a mixed-methods approach, the study employed convergent parallel design via parallel sampling techniques to gather insights. Three hundred and twenty-nine questionnaires were disseminated via online surveys using simple random sampling from 1,584 employees. The questionnaires returned were then accepted based on the comprehension of KM concepts for KMS implementation to introduce KM practice. Quantitative data was subjected to descriptive analysis using SPSS. Qualitative data underwent thematic analysis using Atlas TI. The findings of this study show that Namibia's two MT companies stand to gain significant advantages by implementing KM practices based on their understanding and implementation of KM. By enhancing their KM capabilities, these companies can leverage this organisational knowledge (OK) to drive innovation and adequately meet the demands of a fiercely competitive, knowledge-based society (KBS). This article is of significant value to KM scholars, professionals, decision-makers, and policymakers as an introductory guide to the comprehension of KM for KMS and how they can facilitate effective KM practices within Namibia.